2015
DOI: 10.3897/phytokeys.50.4940
|View full text |Cite
|
Sign up to set email alerts
|

The resurrection of Neohattoria Kamim. (Jubulaceae, Marchantiophyta): a six decade systematic conflict resolved through a molecular perspective

Abstract: The systematic placement of Frullania herzogii has been contentious since its description six decades ago. Over the years it has been interpreted as either a member of the genus Frullania or segregated into its own genus, Neohattoria, due to morphological similarities with both Frullania and Jubula. Here we provide molecular evidence that supports the recognition of the genus Neohattoria and its inclusion within the Jubulaceae, together with Jubula and Nipponolejeunea. Jubulaceae are placed sister to Lejeuneac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In this classification the genera Amphijubula, Neohattoria, Schusterella, and Steerea are considered to be synonymous with Frullania. A later molecular phylogenetic study of the Jubulineae by Larraín et al (2015), however, demonstrated Frullania herzogii S.Hatt. (≡Neohattoria herzogii) to have a sister position within the Jubulaceae with Nipponolejeunea S.Hatt., thus reinstating the genus Neohattoria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this classification the genera Amphijubula, Neohattoria, Schusterella, and Steerea are considered to be synonymous with Frullania. A later molecular phylogenetic study of the Jubulineae by Larraín et al (2015), however, demonstrated Frullania herzogii S.Hatt. (≡Neohattoria herzogii) to have a sister position within the Jubulaceae with Nipponolejeunea S.Hatt., thus reinstating the genus Neohattoria.…”
Section: Discussionmentioning
confidence: 99%
“…The joining of Amphijubula, Schusterella and Steerea within Frullania enabled a rather straightforward assignment of extant species having the relevant morphology to one of the two lineages -Frullaniaceae or Jubulaceae -based on the distinctions listed in Larraín et al (2015). These include:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomenclature of initial branching appendages follow von Konrat & Braggins (2001). For the production of microscopic images we used the same set up and protocols as described in Larraín et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Of the seven families, four have diversity in the hundreds of species, the Lejeuneaceae in particular probably comprises in excess of 1000 species, and the other three families have diversity lower by orders of magnitude. The Jubulaceae has four species in two genera (Patch et al 2010;Larraín et al 2015), the Lepidolaenaceae around 20 species in three genera, and the Goebeliellaceae a single species, Goebeliella cornigera (Mitt.) Steph.…”
Section: Introductionmentioning
confidence: 99%